The genotype–phenotype correlations of the CACNA1A-related neurodevelopmental disorders: a small case series and literature reviews - Kessi, Miriam; Chen, Baiyu; Pang, Nan; Yang, Lifen; Peng, Jing; He, Fang; Yin, Fei (Frontiers in Molecular Neuroscience, 2023)
Background Genotype–phenotype correlations of the CACNA1A-related neurodevelopmental disorders such as global developmental delay (GDD)/intellectual disability (ID), epileptic encephalopathy (EE), and autism spectrum disorder (ASD) are unknown. We aimed to summarize genotype–phenotype correlations and potential treatment for CACNA1A-related neurodevelopmental disorders. Methods Six children diagnosed with CACNA1A-related neurodevelopmental disorders at Xiangya Hospital, Central South University from April 2018 to July 2021 were enrolled. The PubMed database was systematically searched for all reported patients with CACNA1A-related neurodevelopmental disorders until February 2023. Thereafter, we divided patients into several groups for comparison. Results Six patients were recruited from our hospital. Three cases presented with epilepsy, five with GDD/ID, five with ataxia, and two with ASD. The variants included p.G701R, p.R279C, p.D1644N, p.Y62C, p.L1422Sfs*8, and p. R1664Q [two gain-of-function (GOF) and four loss-of-function (LOF) variants]. About 187 individuals with GDD/ID harboring 123 variants were found (case series plus data from literature). Of those 123 variants, p.A713T and p.R1664* were recurrent, 37 were LOF, and 7 were GOF. GOF variants were linked with severe-profound GDD/ID while LOF variants were associated with mild–moderate GDD/ID (p = 0.001). The p.A713T variant correlated with severe-profound GDD/ID (p = 0.003). A total of 130 epileptic patients harboring 83 variants were identified. The epileptic manifestations included status epilepticus (n = 64), provoked seizures (n = 49), focal seizures (n = 37), EE (n = 29), absence seizures (n = 26), and myoclonic seizures (n = 10). About 49 (42.20%) patients had controlled seizures while 67 (57.80%) individuals remained with refractory seizures. Status epilepticus correlated with variants located on S4, S5, and S6 (p = 0.000). Among the 83 epilepsy-related variants, 23 were recurrent, 32 were LOF, and 11 were GOF. Status epilepticus was linked with GOF variants (p = 0.000). LOF variants were associated with absence seizures (p = 0.000). Six patients died at an early age (3 months to ≤5 years). We found 18 children with ASD. Thirteen variants including recurrent ones were identified in those 18 cases. GOF changes were more linked to ASD. Conclusion The p.A713T variant is linked with severe-profound GDD/ID. More than half of CACNA1A-related epilepsy is refractory. The most common epileptic manifestation is status epilepticus, which correlates with variants located on S4, S5, and S6.